2003
DOI: 10.1186/cc2184
|View full text |Cite
|
Sign up to set email alerts
|

Conventional or physicochemical approach in intensive care unit patients with metabolic acidosis

Abstract: IntroductionMetabolic acidosis is the most frequent acid–base disorder in the intensive care unit. The optimal analysis of the underlying mechanisms is unknown.AimTo compare the conventional approach with the physicochemical approach in quantifying complicated metabolic acidosis in patients in the intensive care unitPatients and methodsWe included 50 consecutive patients with a metabolic acidosis (standard base excess ≤ -5). We measured sodium, potassium, calcium, magnesium, chloride, lactate, creatinine, urea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(31 citation statements)
references
References 17 publications
2
28
0
1
Order By: Relevance
“…However, we should keep in mind that AG is the sum of dissociated, non-volatile weak acids (albumin and phosphate), lactate and unmeasured anions. Therefore, to quantify unmeasured anions properly, the AG should be adjusted for weak acids (mainly albumin) and lactate should be subtracted 11. For this reason, we believe that AG, SIG or even the Cl − /Na + ratio should be used to determine the moment of DKA resolution as opposed to using pH or bicarbonate.…”
Section: Discussionmentioning
confidence: 99%
“…However, we should keep in mind that AG is the sum of dissociated, non-volatile weak acids (albumin and phosphate), lactate and unmeasured anions. Therefore, to quantify unmeasured anions properly, the AG should be adjusted for weak acids (mainly albumin) and lactate should be subtracted 11. For this reason, we believe that AG, SIG or even the Cl − /Na + ratio should be used to determine the moment of DKA resolution as opposed to using pH or bicarbonate.…”
Section: Discussionmentioning
confidence: 99%
“…High anion gap acidosis (13%) was detected in cases of normal SIG. there was also moderate correlation between the ALAG and SIG (r = 0.51) where other studies found higher correlation between them [13,14,24]. Fencl et al [13] had already demonstrated that BE fails as a measure of metabolic acidosis when there is a change in the plasma concentration of the non-bicarbonate buffers, an almost universal disorder in critically ill patients.…”
Section: Discussionmentioning
confidence: 93%
“…there was also moderate correlation between the ALAG and SIG (r = 0.51) where other studies found higher correlation between them [13,14,24]. Fencl et al [13] had already demonstrated that BE fails as a measure of metabolic acidosis when there is a change in the plasma concentration of the non-bicarbonate buffers, an almost universal disorder in critically ill patients. Kellum [20,22,23] considered that both methods yield virtually identical results, despite a different conceptual approach to underlying mechanisms.…”
Section: Discussionmentioning
confidence: 93%
“…Second, no quantitative assessment of the secondary responses to primary changes in acid-base status is offered by the physicochemical approach [28]. Nevertheless, several studies [15], [16], [17], [29] have demonstrated that the Stewart's approach to acid-base disturbances allows the differentiation between tissue acidosis and hyperchloremic acidosis, and then results in identification of more patients with major acid-base disorders than the traditional evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the Stewart's approach is a time-consuming method and unsuitable at the bedside. Previous studies [16], [17] have shown that strong ion gap (SIG) could be substituted by the anion gap corrected for albumin and lactate (AG corr ). Furthermore, recently, Nagaoka et al [18] suggested that the difference between sodium and chloride concentrations ([Na + ] – [Cl − ]) could be used as a surrogate of SID.…”
Section: Introductionmentioning
confidence: 99%